The influence of roof lithology on the fracture propagation of horizontal well multistage fracturing in the roof of broken soft coal seams. Issue 1 (1st January 2023) - Li, X J; Zhao, H F; Liu, C S; Xiong, Y G; Lan, J L; Han, H
Abstract: Horizontal well multistage fracturing in the roof of broken soft coal seams has been demonstrated to be an effective technique to extract coalbed methane (CBM). However, fracture propagation behaviours under this technology vary significantly with different roof lithologies. Therefore, the influence of roof lithology on fracture propagation was investigated in this study. Based on the No. 5 and No. 11 coal seams in the Hancheng block of the Ordos Basin in China, field tests of horizontal well multistage fracturing in the sandstone and mudstone roof of crushed soft coal seams were performed and fractures were detected by microseismic monitoring. Corresponding hydraulic fracturing physical simulation experiments were conducted. The results show that the effectively propped fractures in the roof can provide flow channels for CBM. The better microseismic monitoring fractures and higher CBM production than direct fracturing in coal seams demonstrated the desirable feasibility of this technology. For the sandstone roof, the morphologies of hydraulic fractures were regular and one main fracture was formed by each perforation cluster. For the mudstone roof, the shapes of fractures were irregular and complicated fracture networks were formed. The findings can improve the design of horizontal well multistage fracturing in the roof of broken soft coal seams.